Fabrication And Characterization Of Black Silicon For Heterojunction Solar Cells - Abdulkadir, Auwal (2022)
Black silicon (b-Si) is a promising technology that reduces broadband reflection within 300-1100 nm wavelength region and improves light absorption in crystalline silicon (c-Si). B-Si consists of a surface with random nanowires or a combination of nanowires and microtextures (hybrid textures) which leads to a refractive index grading effect at the air/c-Si interface. In this work, electroless metal-assisted chemical etching (MACE) is used to fabricate b-Si. One-step MACE, two-step MACE and hybrid microtextures/nanotextures investigating different effects such as etching time, etchants concentration, silver nanoparticles (Ag NPs) layer thickness towards surface morphological and optical properties (within 300-1100 nm wavelength region) of the b-Si are carried out. Two step MACE involve shorter AgNO3:HF dip time. The hybrid texturing involves prior etching in NaOH to produce pyramids. For one-step MACE, nanowires with an average length of ~2.9 μm and an average diameter of ~120 nm are demonstrated. Weighted average reflection (WAR) of 6.0% has been realized. For two-step MACE, nanowires with an average length of 577 nm and diameter of ~200 nm are produced with WAR of ~5.5%.